Prevalence, Magnitude, and Genotype Distribution of Urinary Cytomegalovirus (CMV) Shedding Among CMV-Seropositive Children and Adolescents in the United States. (5th June 2019) - White, Jodie L; Patel, Eshan U; Abraham, Alison G; Grabowski, Mary Kate; Arav-Boger, Ravit; Avery, Robin K; Quinn, Thomas C; Tobian, Aaron A R
Abstract: Background: There are limited nationally representative data on correlates of cytomegalovirus (CMV) shedding among children and adolescents. In addition, the genotype distribution of CMV infections has not been well characterized among general populations in the United States Methods: This study characterized urinary CMV shedding among CMV immunoglobulin G-positive 6- to 19-year-olds in the US household population using data from the 1999–2004 National Health and Nutrition Examination Survey (NHANES). Multivariable Poisson regression was used to estimate adjusted prevalence ratios (aPR) and corresponding 95% confidence intervals (CIs). Analyses were weighted and multiple imputation was performed to handle missing data (with the exception of CMV genotypes). Results: Prevalence of urinary CMV shedding was significantly lower among 9- to 11-year-olds (20.6%; aPR = 0.61; 95% CI, 0.44–0.83) and 12- to 19-year-olds (7.0%; aPR = 0.21; 95% CI, 0.14–0.30) compared with 6- to 8-year-olds (34.4%). Among CMV shedders, the youngest age group also had the highest urinary CMV viral loads. The prevalence of urinary CMV shedding among obese individuals was significantly lower compared with lean individuals (aPR = 0.68; 95% CI, 0.47–0.99). Among CMV shedders, glycoprotein B (gB)1 (51%) was the most prevalent gB variant, followed by gB2 (29%), gB3 (21%), and gB4 (13%); glycoprotein H (gH)2 (60%) was more prevalent than gH1 (48%). Multiple (≥2) gB (14%) and multiple gH (7%) infections were detected among CMV shedders. Conclusions: This study underscores the importance of young children even above the age of 5 years as a potential source of CMV transmission. The detection of multiple CMV strains among CMV shedders may have implications for the transmission of viral diversity as well as vaccine development.